Comparison of Antioxidant Activity of Dracocephalum polychaetum Bornm and Nepeta cataria L. and Their Effect on Probiotic Bacteria in a Simulated Gastrointestinal Environment - Fatemeh Shahdadi; Maryam Payandeh; Ali Salehi Sardoei (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Dracocephalum polychaetum Bornm and Nepeta cataria L. are two plants from the Lamiaceae family with antibacterial, antifungal, and antiviral properties. This study evaluated the phenolic compounds, antioxidant activity, and effect of aqueous extracts on the survival of Lactobacillus acidophilus and Bifidobacterium animalis in a simulated gastrointestinal environment. Method: The aerial parts of plants were collected at the vegetative growth stage from the Hanza-Kuh's highlands in the Bahr Asman region of Jiroft city, Iran, in spring 2018. The total phenolic content of plants and antioxidant activity were measured using Folin–Ciocalteau and DPPH (2, 2-diphenyl-1-picrylhydrazyl) methods, respectively. For investigating the survival of probiotic bacteria in a simulated gastrointestinal environment, bacterial suspension was inserted into tubes containing 0, 100, 250, 500, and 1000 ppm of extracts and then incubated in a simulated gastrointestinal environment. The probiotic bacteria were counted using an MRS agar medium at various incubation times. Results: The results showed that the amount of total phenolic compounds in the D. polychaetum Bornm extract (44.55 mg/g dry matter) was higher than that of N. cataria L. (18.37 mg/g dry matter). With increased extracts concentrations, the percentage of DPPH-free radicals increased, and D. polychaetum Bornm extract in all concentrations showed higher DPPH free radical inhibitory content compared to the N. cataria L. extract. The viability results in the same gastrointestinal environment showed that samples containing N. cataria extract had a more remarkable survival rate than the controls and D. polychaetum Bornm extract. Conclusion: Using less than 500 ppm of D. polychaetum Bornm and N. cataria L. aqueous extracts can increase probiotic bacteria growth and viability.